Dairy calcium intake and lifestyle risk factors for bone loss in hiv-infected and uninfected mediterranean subjects - Vecchi Valentina (BMC Infectious Diseases, 2012)
Abstract Background Despite the reported high prevalence of osteoporosis in the human immunodeficiency virus (HIV)-population, there have been no previous studies examining dairy calcium intake and bone mineral density (BMD) in HIV-subjects. We assessed the prevalence of low BMD in HIV-infected and uninfected subjects and analyzed the effects of calcium intake, lifestyle and HIV-related risk factors on BMD. Methods One hundred and twelve HIV-infected subjects were consecutively enrolled. Seventy- six HIV-uninfected subjects matched for age and sex were enrolled as the control group. The HIV-subjects were interviewed about lifestyle habits and completed a weekly food-frequency questionnaire to estimate calcium intake. HIV-RNA, CD4+ T-cell count and data on antiretroviral therapy were also recorded. Both biochemical bone turnover markers and BMD, assessed by dual-energy radiographic absorptiometry (DXA) were recorded in the HIV-cases and controls. We also calculated the 10-year fracture risks using the WHO FRAX equation. Results Osteoporosis prevalence was significantly higher in the HIV-cases than controls (p < 0.05). BMI values were positively correlated with BMD (p < 0.05). Vitamin D levels were lower in the HIV-subjects (p < 0.02). No correlation was found with daily calcium intake. BMI values were significantly correlated with dairy intake quartiles (p < 0.003). In HIV-subjects, the mean of FRAX score was 1.2 % for hip and 4.7 % for major osteoporotic fractures. On multivariate analysis of the lumbar spine DXA T-score, age (p < 0.005) and HIV/hepatitis C virus co-infection (p < 0.0001) were negatively correlated with BMD, while yogurt intake was a protective predictor of BMD (p < 0.05). In the femur DXA T-score, age (p < 0.01), nadir CD4 + T-cell count < 200 cells/μL (p < 0.05) and drug addiction ( p < 0.0001) were negatively correlated with BMD. Conclusions Among the foods rich in calcium, yogurt was a protective predictor of BMD in HIV-subjects. HIV/HCV co-infection, nadir CD4 + T-cell count < 200 cells/μL and drug addiction were independent predictors of severe BMD. Promoting behavioral changes in food intake and lifestyle, aimed at the primary prevention of bone disease in the chronically-infected subjects seems to be essential for implementing medical intervention in these cases.